Title Page Design with the Triumph of the Art Painting - Auteur inconnu (Rijksmuseum, 1725)
Oeuvre issue des collections Rijksmuseum / Orsay via Europeana pour la demo du fonds documentaire.
http://creativecommons.org/publicdomain/mark/1.0/
Keywords: rijksmuseum; orsay; europeana; oeuvre d'art; musee